DCOne as an Allogeneic Cell-based Vaccine for Multiple Myeloma. Issue 9 (November 2017) - Leaf, Rebecca Karp; Stroopinsky, Dina; Pyzer, Athalia R.; Kruisbeek, Ada M.; van Wetering, Sandra; Washington, Abigail; Ephraim, Adam; Cole, Leandra; Morin, Adam; Jain, Salvia; Nahas, Myrna R.; Apel, Arik; et al.
Abstract : Multiple myeloma (MM) is characterized by progressive immune dysregulation, loss of myeloma-specific immunity, and an immunosuppressive milieu that fosters disease growth and immune escape. Accordingly, cancer vaccines that reverse tumor-associated immune suppression represent a promising therapeutic avenue of investigation. We examined the potential of an allogeneic cellular vaccine to generate immune responses against MM tumor cells. The DCOne vaccine is comprised of a human myeloid leukemia cell line differentiated into a fully functional dendritic cell, expressing a range of tumor-associated antigens that are also known targets in MM. We found that the myeloma-specific antigens expressed by the DCOne vaccine can traffic via extracellular vesicles to surrounding antigen-presenting cells, thus stimulating autologous T-cell responses. Indeed, coculture of peripheral blood mononuclear cells from patients with MM with the DCOne vaccine resulted in the expansion of activated CD8 + T cells expressing interferon-γ and perforin, with no significant change in the percentage of CD4 + T cells producing interleukin-10. Further, coculture of patient's tumor cells with peripheral blood mononuclear cells and DCOne induced cytotoxic T-lymphocyte-mediated killing of autologous MM cells. These findings demonstrate that the allogeneic DCOne vaccine can induce T-cell activation and myeloma-specific immunity via cross presentation of antigens by native antigen-presenting cells.